A triple-source CT system for micro-scale investigation of geological materials: A simulation study. (December 2022) - Gao, Xu-Guang; Sha, Jun-Feng; Luan, Ji-Yuan; Li, Meng-Chen; Wang, Ji-Peng
Abstract: A triple-source CT system is proposed for micro-scale testing of geological materials. This study aims at reducing the projection acquisition time by two-thirds compared to a conventional single-source CT system. The proposed system with different positioning errors in the source-to-object distance ( SOD ) was simulated and tested using the Shepp-Logan phantom model, as well as slices of sand, glass beads, and concrete samples. Furthermore, the imaging quality of a single-source and the triple-source CT system with different dead detector pixels was compared. The results showed that within the maximum allowable positioning error, the pixel differences between the simulated and the original images are close to zero, and the structural similarities are greater than 0.96. In the presence of dead detector pixels, the quality of the simulated images in the triple-source CT system is superior to that of a single-source CT system. The presented triple-source CT system performs well in high-quality image reconstruction. Highlights: A triple-source micro-CT system for imaging geological materials is proposed. Two-thirds reduction in projection acquisition time is achieved compared to a single-source CT system. Effects of positioning errors and dead detector pixels on image reconstruction are examined.